Menelaah Proyek-Proyek Penelitian dan Pengembangan Digital Library - Tafqihan, Zuhdy (Pustakaloka, 2009)
The rapid of development information technology motivates the providers of informationto offer information more quickly and accurately as well as encompass information network widely. As the one information providers, library has to rethink about the precist form of information dissemination to answer the challenge. One the attemps is by performing digital library. In almost two decades, recently many researches on digital library have been carried out and also followed by enhancement projects.